2017
DOI: 10.1007/s00148-017-0636-1
|View full text |Cite
|
Sign up to set email alerts
|

The fiscal impact of immigration to welfare states of the Scandinavian type

Abstract: In this paper, we examine the potential of immigration to strengthen fiscal sustainability, which is under pressure by an ageing population in many European countries. We look at a particularly challenging case, namely that of Denmark, which has extensive tax-financed welfare programmes that provide a high social safety net. The analysis is based on a forecast of the entire Danish economy made using a dynamic computable general equilibrium model with overlapping generations. We present life cycle estimates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 6 publications
0
27
0
1
Order By: Relevance
“…Hansen et al. (: 949) estimated the negative fiscal impact of the entire non‐Western population group (immigrants plus descendants – mostly second generation) residing in Denmark to be around 1 per cent of GDP in 2014. According to the projections, the NPV of lifetime contributions for the 2013 cohort is only positive in the case of Western immigrants and their descendants, all other groups including natives make a negative net contribution.…”
Section: Refugee Migration Is Very Unlikely To Results In a Positive Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Hansen et al. (: 949) estimated the negative fiscal impact of the entire non‐Western population group (immigrants plus descendants – mostly second generation) residing in Denmark to be around 1 per cent of GDP in 2014. According to the projections, the NPV of lifetime contributions for the 2013 cohort is only positive in the case of Western immigrants and their descendants, all other groups including natives make a negative net contribution.…”
Section: Refugee Migration Is Very Unlikely To Results In a Positive Fmentioning
confidence: 99%
“…Often this distinction is practically made between EU and non‐EU migrants – the main reason behind is the nature of available statistical data. These estimates resulted in uniform findings: the net fiscal contribution of non‐Western immigrants is usually negative and is much worse than the contribution of the Western migrants (Wadensjö, ; Gerdes, ; Dustmann and Frattini, ; Hansen et al., ).…”
Section: Fiscal Balance Estimates – Measurements and Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, studies showed that this increased poverty rates among newcomers, although it also was associated with slightly higher employment rates, as intended (Andersen et al, 2012).…”
Section: Sweden: the Challenge Of Flexibilitymentioning
confidence: 90%
“…The majority of studies in the literature deals with this problem by simply estimating the fiscal net contribution, and trusting this to be at least a fair proxy for the effect of interest (see reviews by Rowthorn 2008;Preston 2014). A minority take the alternative approach of attempting to explicitly model the most important dynamic mechanisms that create the difference between the net contribution and the effect (e.g., Storesletten 2000; Miller 1998, 2000;Hansen et al 2017). The obvious weakness of this strategy is that there are many candidate mechanisms, and the exact form is not well known for any of them.…”
Section: Methodsmentioning
confidence: 99%